Answer:
![a=(n^2-P^2n)/(P^2-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4oyd7ntk400d7h5vf8wzt5cntwo0aeaorv.png)
Explanation:
Given equation:
![P=\sqrt{(n^2+a)/(n+a)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/txgmxou878zvyu2yyqbb7a3238u3ciwfxs.png)
Square both sides of the equation:
![\implies P^2=(n^2+a)/(n+a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/7akc5p5dfg0xnp7mhatb9raxdjka95d1yg.png)
Multiply both sides by (n + a):
![\implies P^2(n+a)=n^2+a](https://img.qammunity.org/2023/formulas/mathematics/high-school/hdamui8gi96uw0xy9jlc6ecsbtcg0cwnez.png)
Expand the parentheses:
![\implies P^2n+P^2a=n^2+a](https://img.qammunity.org/2023/formulas/mathematics/high-school/z8rj16jt9ml2sub6qf6v6xfvjuy9nwuw0x.png)
Subtract a from both sides:
![\implies P^2n+P^2a-a=n^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/vghwjpb4wzp1sueycqa329uiwtctab7pxl.png)
Subtract P²n from both sides:
![\implies P^2a-a=n^2-P^2n](https://img.qammunity.org/2023/formulas/mathematics/high-school/e77um5nuu5crq7km8iqk6hozmk5t0p7dhi.png)
Factor out a on the left side of the equation:
![\implies a(P^2-1)=n^2-P^2n](https://img.qammunity.org/2023/formulas/mathematics/high-school/f74fo4vdii2p5deifi1n20pyig0flhfgpk.png)
Divide both sides by (P² - 1):
![\implies a=(n^2-P^2n)/(P^2-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/gj5wznp5yh4zciiotpuy0cmt5qst3rst0t.png)